Vol. 90 : Deterministic Chaos in One-Dimensional Continuous Systems; World Scientific Series on Nonlinear Science. Series A - Awrejcewicz J. Jan; Krysko V. A. Vadim; Papkova I. V. Irina; Krysko A. V. Anton Vadimovich
Title screen